Starch intake and caries increment: A longitudinal study in Finnish adults - FH Jangda; AL Suominen; A Lundqvist; S Männistö; A Golkari; E Bernabé
ABSTRACT Objective: To evaluate whether changes in starch intake (in terms of amount and food sources) were associated with increments in dental caries among adults. Design: 11-year longitudinal study (2000-2011) with duplicate assessments for all variables. A 128-item food frequency questionnaire was used to estimate intake of starch (g/day) and six starch-rich food groups (potatoes, potato products, roots and tubers, pasta, wholegrains, and legumes). Dental caries was assessed through clinical examinations and summarised using the number of decayed, missing and filled teeth (DMFT score). The relationship between quintiles of starch intake and DMFT score was tested in linear hybrid models adjusting for confounders. Setting: Northern and Southern regions of Finland. Participants: 922 adults, aged 30-88 years. Results: Mean starch intake was 127.6 (SD: 47.8) g/day at baseline and 120.7 (55.8) g/day at follow-up. Mean DMFT score was 21.7 (6.4) and 22.4 (6.2) at baseline and follow-up. Starch intake was inversely associated with DMFT score cross-sectionally (rate ratio for highest versus lowest quintile of intake: -2.73, 95%CI: -4.64, -0.82) but not longitudinally (0.32, 95%CI: -0.12, 0.76). By food sources, the intakes of pasta (-2.77, 95%CI: -4.21, -1.32) and wholegrains (-1.91, 95%CI: -3.38, -0.45) were negatively associated with DMFT score cross-sectionally but not longitudinally (0.03, 95%CI: -0.33, 0.39 and -0.10, 95%CI: -0.44, 0.24, respectively). Conclusion: Changes in the amount and sources of starch intake were not associated with changes in dental caries. Further studies should be conducted in different settings and age groups while focusing on starch digestibility and specific sources of starch.